Réponses

  • Omnes
  • Modérateur confirmé
2014-03-16T14:59:17+01:00
Salut,

A (x) = (x -4) (3x +1) - (4 - 5x) (2x +3)
A(x) = 3x² + x - 12x - 4 - (8x + 12 -10x² -15x)
A(x) = 3x² - 11x - 4 - ( -7x + 12 -10x²)
A(x) = 3x² - 11x - 4 + 7x - 12 + 10x²
A(x) = 13x² - 4x - 16

B (x) = (2x -3)² - (x +4)²
B(x) = 4x² - 12x + 9 - (x² + 8x + 16)
B(x) = 4x² - 12x + 9 - x² - 8x - 16
B(x) = 3x² - 20x - 7

C (x) = 3 (2x -1)² - 2 (1+x)²

C(x) = 3(4x² - 4x + 1) - 2(1 + 2x + x²)
C(x) = 12x² - 12x + 3 - (2 + 4x + 2x²)
C(x) = 12x² - 12x + 3 - 2 - 4x - 2x²
C(x) = 10x² - 16x + 1

Bonne journée !